THE PRACTICE of E-COMMERCE IS REGULATED UNDER LAW NUMBER 11 YEAR 2008 - Ni Nyoman Ernita Ratnadewi (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
The practice of electronic commerce or e-commerce regulated under law number 11 of 2008 concerning electronic information and transaction and government regulation number 82 of 2012 concerning implementation of electronic system and transaction. This research armed to find out the practice of e-commerce transaction according to the law and to find out dispute settlement pattern of e-commerce transaction in Indonesia. The normative empirical research method is occupied in this research yet applying statute,  conceptual and sociological approach the research result shown that implementation of electronic transactions are not fully accordance with the existing law and regulation therefore one side defaults are often occurs. Whereas dispute settlement holds the principle of lumping it,  avoidance and negotiation.Keywords : Transaction,  electronic contract